Solid-Phase Extraction Method for the Analysis of Eleven Phenolic Pollutants in Water Samples - Olusoji Olujimi, Olanrewaju; Siyanbola Fatoki, Olalekan; Odendaal, James; Okonkwo, O.J. (Asian Journal of Chemistry, 2010)
An analytical protocol for the determination of priority phenolic compounds: phenol, 2-methyl 4,6-dinitrophenol, 2-chlorophenol, 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol, 2-nitrophenol, 4-nitrophenol, 2,4-dinitrophenol, 4-chloro-3-methylphenol, 2,4,6- tribromophenol and 2,4-dimethylphenol, in water samples using strata C18 cartridge is presented. Different parameters affecting extraction and peak separation were optimized. Recoveries using spiking of the test compounds varied in the ranged between 69.43 ± 1.76 % and 101.87 ± 0.45 %. The high recoveries obtained validated the method. Detection limits obtained ranged from 4 μg L-1 for 2,4-dimethylphenol to 166 μg L-1 for 4-nitrophenol, using LC-UV. The results obtained by applying the developed method to real environmental water sample containing 2,4- dichlorophenol, 2-methyl, 4,6-dinitrophenol, pentachlorophenol and 2,4,6-tribromophenol indicated the following concentration levels: 5.129, 0.561, 4.788 and 0.868 ng μL-1, respectively.